L2 POETRY WRITING IN THE UNIVERSITY CLASSROOM - Varenko Т. (Problems of Engineer-Pedagogical Education, 2020)
The ability to write poetry in a particular language requires and is indicative of the highest level of the language proficiency. This idea brought about a hypothesis that L2 poetry writing could be a valuable tool in training specialists whose professions directly relate to excellent foreign language skills (translators and interpreters, L2 teachers and instructors). Hence, the objectives of this paper are to determine students’ acceptance of and demand for L2 poetry writing as a teaching method and to confirm the above hypothesis that this foreign language teaching and learning methodology can be used as a powerful tool to improve the overall foreign language command, strengthen students’ confidence in themselves in general and their linguistic abilities in particular, enhance their L2 fluency, and boost their motivation for better performance in their studies. The paper reviews and analyses seven different L2 poetry writing activities (illustrative examples provided) practiced with students majoring in English in the university setting in Ukraine. It summarizes the seven-year experiment of curriculum-adapted inclusions of L2 poetry writing activities in the academic process in the L2 university classroom. The activities are collaborating on a play in verse, poetry writing contests, poetry translation contests, ‘bonus’ poems, blogging poetry, newspaper poetry column, ‘collective’ poems. The findings are as follows: implementation of such activities in the academic process is not only favorably accepted by the students, but it also boosts their confidence and fluency in the language they are learning and increases their motivation for better academic performance. The L2 poetry writing activities described in this paper are “plug-and-play” solutions for practitioners and a valuable asset for curriculum-makers in foreign language teaching.